Engineering stability in NADPH oxidases: A common strategy for enzyme production. (17th November 2017) - Ceccon, Marta; Millana Fananas, Elisa; Massari, Marta; Mattevi, Andrea; Magnani, Francesca
Abstract: NADPH oxidases (NOXs) are membrane enzymes whose sole function is the generation of reactive oxygen species. Humans have seven NOX isoenzymes that feature distinct functions in immune response and cell signaling but share the same catalytic core comprising a FAD-binding dehydrogenase domain and a heme-binding transmembrane domain. We previously described a mutation that stabilizes the dehydrogenase domain of a prokaryotic homolog of human NOX5. The thermostable mutant exhibited a large 19 °C increase in the apparent melting temperature (app Tm ) and a much tighter binding of the FAD cofactor, which allowed the crystallization and structure determination of the domain holo-form. Here, we analyze the transferability of this mutation onto prokaryotic and eukaryotic full-length NOX enzymes. We found that the mutation exerts a significative stabilizing effect on the full-length NOX5 from both Cylindrospermum stagnale (app Tm increase of 8 °C) and Homo sapiens (app ΔTm of 2 °C). Enhanced thermal stability resulted in more homogeneous preparations of the bacterial NOX5 with less aggregation problems. Moreover, we also found that the mutation increases the overall expression of recombinant human NOX4 and NOX5 in mammalian cells. Such a 2–5-fold increase is mainly due to the lowered cell toxicity, which leads to higher biomasses. Because of the high sequence identity of the catalytic core within this family of enzymes, this strategy can be a general tool to boost the production of all NOXs.